Analysis How Liquidity, Profitability, and Solvability Ratios Affect Manufacturing Companies Stock Values Listed on the Stock Exchange of Indonesia - Vivin Hanitha; Hendra Hendra; Tri Angreni (eCo-Fin, 2026)
The study employs a quantitative methodology and analyses secondary data from financial reports from businesses. Ten businesses are selected as research samples using the sampling technique's purposive sampling. Using SPSS version 27, the data analysis method employs multiple linear regression. With a regression coefficient of -0.732 and a significance value of 0.007, the findings of the regression analysis demonstrate that the liquidity variable, represented by the Current Ratio (CR), has a negative and substantial impact on stock value. With a regression coefficient of -1.923 and a significance value of 0.230, the solvency variable represented by the Debt to Equity Ratio (DER) has a negative but negligible impact on stock value. With a regression coefficient of 0.253 and a significance value of 0.006, the profitability variable represented by Return on Assets (ROA) has a positive and substantial impact on stock value. According to the simultaneous test results, CR, DER, and ROA collectively have a considerable impact on stock value, with a computed F value of 6.087 at a significance level of 0.002. Furthermore, the coefficient of determination results indicate that the profitability, liquidity, and solvency variables can account for 33.7% of the fluctuation in stock value, with additional variables outside the research model influencing the remaining 66.3%.